보크트-고야나기-하라다 병 환자에서 시행한 유리체강내 덱사메타손 임플란트 삽입술 1예 - 김선도(Seondo Kim), 이은경(Eun Kyoung Lee) (Daihan angwa haghoi jabji, 2018)
목적: 만성적인 재발 경과를 보이는 보크트-고야나기-하라다(Vogt-Koyanagi-Harada, VKH) 병 환자에서 덱사메타손 임플란트 삽입술을 통하여 치료한 1예를 보고하고자 한다. 증례요약: 39세 여자 환자가 일주일 전부터 시작된 두통과 이명이 동반된 양안 시력 저하를 주소로 내원하였다. 안저 검사 및 빛간섭 단층촬영상 양안 망막하중격이 동반된 다발성장액망막박리가 관찰되어 VKH 병으로 진단하였다. 타원에서 고용량 스테로이드 정맥 주입 치료를 시행받은 이후 스테로이드 경구 요법과 면역억제제 병합 치료를 하였으나 잦은 재발을 보였고, 환자는 스테로이드제의 장기간 투여로 인한 부작용을 호소하였다. 이에 3주 간격으로 양안 유리체강내 덱사메타손 임플란트 삽입술을 시행하였다. 삽입술 시행 1개월 후 전방 염증과 유리체 혼탁이 호전되었고, 삽입술 시행 6개월이 지난 마지막 외래 경과 관찰 시까지 경구 스테로이드를 감량한 상태로 유의한 재발 없이 경과 관찰 중이다. 결론: VKH 병 환자에서 스테로이드와 면역억제제 치료에도 불구하고 만성적으로 재발하거나, 부작용으로 장기치료를 유지하기 어려운 경우 덱사메타손 임플란트 삽입술은 좋은 치료적 대안이 되리라 생각한다. Purpose: To report a case of Vogt-Koyanagi-Harada (VKH) disease with chronic recurrence, which was treated with intravitreal dexamethasone implantation. Case summary: A 39-year-old female presented with decreased visual acuities in both eyes accompanied by headaches and tinnitus the previous week. On fundus examination and optical coherence tomography, multiple serous retinal detachments with subretinal septa were observed in both eyes, and she was diagnosed with VKH disease. After undergoing high dose intravenous steroid therapy at another hospital, she was treated with oral prednisolone and immunosuppressant drugs. However, she showed frequent recurrences, and also complained of side effects from prolonged systemic steroids. We then performed intravitreal injections of dexamethasone implants in both eyes at 3-week intervals. One month following the injections, the inflammations in the anterior chamber and vitreous opacities were improved. Until the last visit at 6 months after the injection, there was no significant recurrence of inflammation, although oral prednisolone had been tapered. Conclusions: In VKH disease, intravitreal dexamethasone implantation may be an effective treatment option if chronic recurrence occurs, despite systemic steroid and immunosuppressant therapy or sustained treatment being difficult to maintain because of side effects. KCI Citation Count: 0